Czech Republic : Technical Note on Macroprudential Policy Framework. (IMF Staff Country Reports; Country Report, 2012)
This technical note examines the macroprudential policy framework in the Czech Republic. The Czech National Bank (CNB) has been actively developing its macroprudential policy framework for some time, including most recently the establishment of a separate Financial Stability Department. The authorities' first line of defense against threats to financial stability has been sound macroeconomic policies. The Czech financial system overall appears stable. Stress tests indicate that banks would have sufficient capital and liquidity buffers to withstand a double-dip recession.